Efektivitas Kinerja Aparatur Desa dalam Pelayanan Publik Kepada Masyarakat di Desa Balongsari - Diana Noviyanti; Haura Atthahara; Sopyan Resmana Adiarsa; Evi Priyanti (Jurnal Ilmiah Wahana Pendidikan, 2022)
Employee performance is the ability of employees when carrying out their functions and duties, this performance is a measure of the success of employees in providing services to the community. The village office is an agency which in its implementation is close or in direct contact with the needs and interests of the community. Balongsari Village is one of the 13 villages in the District of Rawamerta, Karawang Regency. The purpose of this study is that researchers want to find out how the effectiveness of the performance of the Balongsari Village apparatus in public services in terms of five aspect indicators. The research method used in this study is a qualitative method. The results of this study indicate that the performance of the Balongsari Village apparatus has been effective when viewed from the theory according to Mitchel in (Sedarmayanti 2009:51), namely the quality of work, accuracy in completing work, initiative in completing work, ability to complete work, and ability to foster cooperation with other party. The Balongsari Village Office is no different from other village offices in the context of carrying out its duties and functions. However, different things can be seen from the skills and work abilities possessed by each Balongsari Village apparatus. The services at the Balongsari Village Office are still not good, this situation is described by the work pattern shown by the existing employees or apparatus. So that people feel that the services in Balongsari Village require a long process, this is felt by the community when they want to get services regarding the making of letters and also Family Cards. However, Balongsari Village itself is a village that is included in the Advanced Village category and holds a clean village and the best administration.